Genetics and pharmacogenetics in the diagnosis and therapy of cardiovascular diseases - Krasi, Geraldo; Precone, Vincenza; Paolacci, Stefano; Stuppia, Liborio; Nodari, Savina; Romeo, Francesco; Perrone, Marco; Bushati, Vilma; Dautaj, Astrit; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Cardiovascular diseases are the main cause of death worldwide. The ability to accurately define individual susceptibility to these disorders is therefore of strategic importance. Linkage analysis and genome-wide association studies have been useful for the identification of genes related to cardiovascular diseases. The identification of variants predisposing to cardiovascular diseases contributes to the risk profile and the possibility of tailored preventive or therapeutic strategies. Molecular genetics and pharmacogenetics are playing an increasingly important role in the correct clinical management of patients. For instance, genetic testing can identify variants that influence how patients metabolize medications, making it possible to prescribe personalized, safer and more efficient treatments, reducing medical costs and improving clinical outcomes. In the near future we can expect a great increment in information and genetic testing, which should be acknowledged as a true branch of diagnostics in cardiology, like hemodynamics and electrophysiology. In this review we summarize the genetics and pharmacogenetics of the main cardiovascular diseases, showing the role played by genetic information in the identification of cardiovascular risk factors and in the diagnosis and therapy of these conditions.